Economic-environmental efficiency of european agriculture: a generalized maximum entropy approach - Moutinho, Victor (2018)
The study aims to estimate the agricultural economic-environmental efficiency (eco-efficiency) for European countries. Eco-efficiency is obtained by the data envelopment analysis (DEA) and stochastic frontier analysis (SFA) using a generalized maximum entropy (GME) approach. Agriculture gross value added (GVA) is considered as the desirable output and greenhouse gas (GHG) emissions as the undesirable output. Capital, labour, land, energy and nutrients are regarded as inputs. The GVA/GHG ratio is the measure of eco-efficiency. The estimation was made for the years 2005 and 2010, which correspond to the 1st year of commitment to the Kyoto Protocol and the most recent year with information concerning all the variables in the study, and is a period that can allow us to see some changes after the agreement. The results show that in 2005, Austria, Slovenia, Hungary, the Netherlands and Portugal revealed the higher levels of eco-efficiency; and countries such as Estonia, Germany, Ireland, Latvia and Slovakia are the group with the lowest levels of eco-efficiency. In 2010, Bulgaria, Finland, Greece, the Netherlands and Portugal are the group of countries with the higher levels of eco-efficiency, while Denmark, Germany, Latvia, Romania and the United Kingdom are the group with the lowest levels of eco-efficiency.